Analisis Persepsi Masyarakat Terhadap Produk-Produk Perbankan Syariah: Studi Kasus pada Masyarakat Desa Sei Rotan - Raya Sari Lubis; Sarwo Edi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to understand the perceptions of the Sei Rotan Village community towards Islamic banking products and the factors that influence their acceptance and utilization. This qualitative research with a descriptive approach was conducted in Sei Rotan Village, Percut Sei Tuan Sub-district, Deli Serdang Regency, North Sumatra Province. Data were collected through interviews with resource persons from various circles, including community leaders and local entrepreneurs. The results show that most people are aware of the existence of Islamic banks, but the understanding of the products offered still varies. Some have accounts in Islamic banks and understand products such as wadiah savings and Islamic financing, while others only have general knowledge. Some interviewees expressed interest in opening an account at an Islamic bank in the future because they want to avoid usury and transact according to Islamic principles. Factors that influence people's perceptions include knowledge, interest and needs. Limited knowledge results in low understanding of Islamic banking products, while interest is influenced by religious awareness. The need for Islamic banking services also influences people's decisions, where those who feel the need are more interested in using Islamic bank services. The conclusion of this study shows that although there is awareness about Islamic banking, efforts are needed to improve people's understanding of Islamic banking products to encourage wider acceptance and utilization.